A secure and efficient data transmission technique using quantum key distribution - Armanuzzaman, Md; Alam, Kazi Md Rokibul; Hassan, Md Mehadi; Morimoto, Yasuhiko (NSysS : proceedings of 2017 4th International Conference on Networking, Systems and Security : 18-20 December, 2017, Dhaka, Bangladesh, 2017)
This paper proposes a new data transmission technique that uses Quantum Key Distribution (QKD) method, One Time Pad (OTP) encryption technique and Huffman encoding compression algorithm to transmit the data more securely and efficiently. While data is transmitted, requirements like secrecy, less overhead through compression etc are crucial issues. QKD is one of the most promising methods which provide unconditional security. It relies upon the immutable laws of quantum physics rather than computational complexity as the basis of its secrecy. To establish the trust between the sender and the receiver, this paper considers a trusted center that distributes and verifies the key. Also it uses Huffman encoding-a lossless compression algorithm to compress the transmitted data over the classical channel that reduces the data transmission overhead. Moreover for data encryption, it applies OTP technique with the key randomly generated by the QKD method that ensures the secrecy of the transmitted data over the classical channel. Thus the overhead of both quantum and classical channels are reduced. Finally the time requirements for encoding-decoding and encryption-decryption for the proposed technique are evaluated.